2015
DOI: 10.1177/2158244015612522
|View full text |Cite
|
Sign up to set email alerts
|

Obese Adults’ Perceptions of News Reporting on Obesity

Abstract: News reporting, in channels such as broadcast and print media, on obesity as an issue has increased dramatically in the last decade. A qualitative study, in which we used in-depth interviews and thematic analysis, was undertaken to explore 142 obese individuals' perceptions of, and responses to, news reporting about obesity. Participants believed that news reporting on obesity focused on personal responsibility and blame, and portrayed obese people as "freaks." They described being portrayed as "enemies" of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 68 publications
0
10
0
2
Order By: Relevance
“…A strength of the study is that the men’s weight loss stories were collected from 4 years so that a complete sample was analysed. This article builds upon previous theoretical and empirical works which have considered the panopticon/synopticon dyad (Couch et al, 2015a, 2015b, 2016, 2017; Doyle, 2011; Mathiesen, 1997, 2004) and extends the synopticon and panopticon by examining a specific story type within the system . While the study considers the stories within a wider system of mediated weight-related content, it does not examine the data surrounding the stories – the advertisements and other editorial that was contained with the magazine.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…A strength of the study is that the men’s weight loss stories were collected from 4 years so that a complete sample was analysed. This article builds upon previous theoretical and empirical works which have considered the panopticon/synopticon dyad (Couch et al, 2015a, 2015b, 2016, 2017; Doyle, 2011; Mathiesen, 1997, 2004) and extends the synopticon and panopticon by examining a specific story type within the system . While the study considers the stories within a wider system of mediated weight-related content, it does not examine the data surrounding the stories – the advertisements and other editorial that was contained with the magazine.…”
Section: Resultsmentioning
confidence: 95%
“…In this way, the weight loss stories we have examined are one part of a larger system of messages around body weight so that audiences experience multiple messages about acceptable and unacceptable body weight. This includes the visual exclusion of obese people’s identity (Cooper, 2007), stigmatising media imagery of obese people (Heuer et al, 2011; McClure et al, 2010), sensationalist news stories about the problem of obesity (Holland et al, 2011; Couch 2015a), online reader comments in response to obesity news reporting (Farrell et al, 2015), online weight loss forums (Bennett and Gough, 2012), the valorisation of the thin ideal (Couch et al, 2016) and advertising of weight loss and body maintenance products and services (Cleland et al, 2002).…”
Section: The Stories Within the Media Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Results indicated that a greater number of negative versus positive images of overweight persons were found, and 72% of images that portrayed an individual with overweight or obesity were stigmatising (e.g., “portrayed as overweight/obese person eating/drinking an unhealthy food/drink”). A further study conducted in Australia sought to investigate the perceptions of 142 obese individuals towards obesity news reporting (Couch, Thomas, Lewis, Blood, & Komesaroff, ). The majority of participants ( N = 122) believed news coverage was “superficial,” “unrealistic,” “inaccurate,” “unfair,” or “unhelpful”; conveyed personal blame and undesirability; and were considered dehumanising and stigmatising among participants.…”
Section: Introductionmentioning
confidence: 99%